2010
DOI: 10.1103/physrevb.81.205437
|View full text |Cite
|
Sign up to set email alerts
|

Current-voltage(IV)characteristics of armchair graphene nanoribbons under uniaxial strain

Abstract: The current-voltage (I-V) characteristics of armchair graphene nanoribbons under a local uniaxial tension are investigated by using first principles quantum transport calculations. It is shown that for a given value of bias-voltage, the resulting current depends strongly on the applied tension. The observed trends are explained by means of changes in the band gaps of the nanoribbons due to the applied uniaxial tension. In the course of plastic deformation, the irreversible structural changes and derivation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(84 citation statements)
references
References 33 publications
9
75
0
Order By: Relevance
“…The electronic transport properties are studied by the non-equilibrium Green's function (NEGF) techniques within the Keldysh formalism as implemented in the TRANSIESTA package. 20,21 The electric current through the contact region is calculated using the Landauer-Buttiker formula 22 = 0 ( , ) To model the phosphorene layer, we used a 3 × 3 surpercell as shown in Fig. 1, which has lattice dimensions of 9.898 Å × 13.854 Å corresponding to the unit cell of 3.3 Å × 4.618 Å, which is in good agreement with previous reports.…”
Section: Methodssupporting
confidence: 65%
“…The electronic transport properties are studied by the non-equilibrium Green's function (NEGF) techniques within the Keldysh formalism as implemented in the TRANSIESTA package. 20,21 The electric current through the contact region is calculated using the Landauer-Buttiker formula 22 = 0 ( , ) To model the phosphorene layer, we used a 3 × 3 surpercell as shown in Fig. 1, which has lattice dimensions of 9.898 Å × 13.854 Å corresponding to the unit cell of 3.3 Å × 4.618 Å, which is in good agreement with previous reports.…”
Section: Methodssupporting
confidence: 65%
“…2 This spin-like valley degree of freedom of graphene has opened up a new avenue in nanoelectronic applications, which is the so-called valleytronics. 4 As a matter of course, the ability to generate valley-polarized current becomes an essential requirement in realizing the valleytronic applications. One way to break the valley symmetry in graphene is by applying a strain to it.…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that most of the works with calculations on the current-voltage characteristics of HANGRs 43,44,92,97 are based on systems A1 (strained electrodes). Only references 43, 92 and 97 study a system of 8 atoms in width, while no literature was found for HAGNR of 11 atoms in width (although it belongs to the same series of 8 atoms and 5 atoms in width, also studied in reference 44).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, strain studies on graphene nanoribbons are gaining much attention as the control of their mechanical deformation could allow the creation of novel devices for energy harvesting [83][84][85][86] . There exist many reports on the electronic structure modification via strain engineering of simulated systems of different edge type, edge decoration, shape, and width [46][47][48][49][50][87][88][89][90][91][92][93][94][95][96] . Among those researchers, some outstand by including analyses of the current-voltage characteristics 43,44,92,97,98 .…”
mentioning
confidence: 99%